Additive manufacturing of smart materials exhibiting 4-D properties: A state of art review. (September 2022) - Kumar, Sudhir; Singh, Rupinder; Batish, Ajay; Singh, TP
This review highlights the additive manufacturing (AM) of smart materials, exhibiting 4-D properties under the affect of external stimulus. The smart materials are special in nature because they acquire different shapes, dimensional features (which may be altered a number of times in controlled fashion) when exposed to different external stimuli. Commercially, a number of smart materials are available that can be AM/3-D printed as metamaterials. Overall, this review outlines the applications of 3-D-printed material with 4-D properties for various applications (like biomedical, engineering, space science, structures, composites, etc.). A case study to evaluate the feasibility for in-house preparation of smart composite feedstock filament for fused deposition modelling-based 3-D printing has been presented for nonstructural engineering applications. The prepared filament in this case study has shown magnetic properties (which are considered essential for smart composite), so that when it may be triggered by external magnetic field to show 4-D behavior.